Gestational Diabetes Mellitus: Clinical Characteristics and Perinatal Outcomes in a Multiethnic Population of North Italy. (26th December 2021) - Caputo, M.; Bullara, V.; Mele, C.; Samà, M. T.; Zavattaro, M.; Ferrero, A.; Daffara, T.; Leone, I.; Giachetti, G.; Antoniotti, V.; Longo, D.; De Pedrini, A.; et al.
Abstract : Aim . To evaluate clinical characteristics and perinatal outcomes in a heterogeneous population of Caucasians born in Italy and High Migration Pressure Countries (HMPC) women with GDM living in Piedmont, North Italy. Methods . We retrospectively analyzed data from 586 women referring to our unit (2015–2020). Epidemiological (age and country of origin) and clinical-metabolic features (height, weight, family history of DM, parity, previous history of GDM, OGTT results, and GDM treatment) were collected. The database of certificates of care at delivery was consulted in relation to neonatal/maternal complications (rates of caesarean sections, APGAR score, fetal malformations, and neonatal anthropometry). Results . 43.2% of women came from HMPC; they were younger p < 0.0001 and required insulin treatment more frequently than Caucasian women born in Italy ( χ 2  = 17.8, p = 0.007 ). Higher fasting and 120-minute OGTT levels and gestational BMI increased the risk of insulin treatment (OGTT T0: OR = 1.04, CI 95% 1.016–1.060, p = 0.005 ; OGTT T120: OR = 1.01, CI 95% 1.002–1.020, p = 0.02 ; BMI: OR = 1.089, CI 95% 1.051–1.129, p < 0.0001 ). Moreover, two or more diagnostic OGTT glucose levels doubled the risk of insulin therapy (OR = 2.03, IC 95% 1.145–3.612, p = 0.016 ). We did not find any association between ethnicities and neonatal/maternal complications. Conclusions . In our multiethnic GDM population, the need for intensive care and insulin treatment is high in HPMC women although the frequency of adverse peripartum and newborn outcomes does not vary among ethnic groups. The need for insulin therapy should be related to different genetic backgrounds, dietary habits, and Nutrition Transition phenomena. Thus, nutritional intervention and insulin treatment need to be tailored.